Read-through transcripts in lung: germline genetic regulation and correlation with the expression of other genes. (11th March 2020) - Maspero, Davide; Dassano, Alice; Pintarelli, Giulia; Noci, Sara; De Cecco, Loris; Incarbone, Matteo; Tosi, Davide; Santambrogio, Luigi; Dragani, Tommaso A; Colombo, Francesca
Abstract: Transcripts originating from the transcriptional read through of two adjacent, similarly oriented genes have been identified in normal and neoplastic tissues, but their functional role and the mechanisms that regulate their expression are mostly unknown. Here, we investigated whether the expression of read-through transcripts previously identified in the non-involved lung tissue of lung adenocarcinoma patients was genetically regulated. Data on genome-wide single nucleotide variant genotypes and expression levels of 10 read-through transcripts in 201 samples of lung tissue were combined to identify expression quantitative trait loci (eQTLs). Then, to identify genes whose expression levels correlated with the 10 read-through transcripts, we used whole transcriptome profiles available for 154 patients. For 8 read-though transcripts, we identified 60 eQTLs (false discovery rate <0.05), including 17 cis -eQTLs and 43 trans -eQTLs. These eQTLs did not maintain their behavior on the 'parental' genes involved in the read-through transcriptional event. The expression levels of 7 read-through transcripts were found to correlate with the expression of other genes: CHIA–PIFO and CTSC–RAB38 correlated with CHIA and RAB38, respectively, while 5 other read-through transcripts correlated with 43 unique non-parental transcripts; thus offering indications about the molecular processes in which these chimeric transcripts may be involved. We confirmed 9 eQTLs (for 4 transcripts) in the non-involved lung tissue from an independent series of 188 lung adenocarcinoma patients. Therefore, this study indicates that the expression of four read-through transcripts in normal lung tissue is under germline genetic regulation, and that this regulation is independent of that of the genes involved in the read-through event. Abstract : We identified 60 quantitative trait loci (eQTLs) whose genotype associated with the expression levels of 8 read-through transcripts (RTTs) that, therefore, are regulated by germline variations. Expression levels of 5 read-through transcripts correlated with the expression of 43 unique, non-parental transcripts. Nine eQTLs regulating four read-through transcripts were validated in an independent patient series.